The Relationship Between Emotional Regulation and Academic Burnout in Universitas Kristen Satya Wacana Students - Glory Angel Manggoa; Heru Astikasari Setya Murti (Universitas PGRI Yogyakarta, 2026)
Negative emotions that arise when experiencing academic burnout need to be managed, a process known as emotional regulation. This study aims to investigate the relationship between emotional regulation and academic burnout among students at Universitas Kristen Satya Wacana. This research employed a quantitative method and a correlational design, with 153 students from Universitas Kristen Satya Wacana as participants. Data is collected using a simple random sampling technique. Emotional regulation was measured with the Emotion Regulation Questionnaire (ERQ) (α = 0.754), and academic burnout was measured with the Maslach Burnout Inventory Student Survey (MBI-SS) (α = 0.846). The results of this study showed a significant value of 0.003 (p < 0.05) and a correlation coefficient of -0.250, indicating that the higher the emotional regulation, the lower the academic burnout felt. This research can serve as a reference for the University to develop academic and non-academic policies that reduce academic pressure. Keywords: emotional regulation, academic burnout, college students